Handling and understanding the horse - Pavord, Marcy (Swan Hill, 1999)
This work aims to explore why horses behave in the way that they do and demonstrates how scientific theory and psychological understanding can be put to practical effect. It offers practical advice on how to handle horses on a day-to-day basis and how to avoid needless cost, anxiety and heartache.